Kajian ulang transfer massa disertai reaksi kimia pada absorpsi reaktif gas CO2 pada packed column - Ali Altway; S Susianto; K Kuswandi; K Kusnaryo (Jurnal Teknik Kimia Indonesia, 2008)
This article reviewed researches have been carried out concerning simulation of enhancement factor for absorption accompanied by second order chemical reaction under non-isothermal condition and modeling of packed column for CO2 absorption in K2CO3 solution. The value of enhancement factor was predicted using eddy diffusivity model (King model) for describing interface mass transfer phenomena. System of differential equations developed in this modeling was solved with Orthogonal Collocation method. The value of E predicted from this research agrees very well with that predicted using Penetration model (Higbie model) by Vas Bhat (1997). The researches concerning packed column modeling was carried out experimentally and theoretically. Experimental works were carried out to validate theoretical prediction. Material studied in this research was CO2 –air mixture and potassium carbonate solution. Potassium carbonate solution was fed into top of the column and the solution was contacted counter currently with rising CO2-air mixture stream. The liquid leaving the column was analyzed by titration. Theoretical studies were carried out by developing microscopic mass and energy balance model on the packed column. The resulted system of first order differential equations were solved using Forth order Runge Kutta method. The solution of this model requires information concerning rate of gas-liquid interface mass transfer where King model was used in this study. Mass transfer, CO2, solubility, kinetics, and reaction equilibrium data required in this theoretical study were obtained from literatures (Danckwertz, 1970; Kohl and Riesenfeld,1985; and Treyball, 1981). In this research, the effect of absorbent flow rate and the concentration of  K2CO3 in the inlet absorbent on percent recovery of CO2  gas was studied.Deviation between simulation prediction results and experimental data was below  10%  for absorbent flow rate of 3 to  5 liter/menit and for absorbent flow rate of 5 to  7 liter/ menit the deviation was between 10 and 30%. Key words: mass transfer, eddy diffusivity, absorption, non-isotermal, packed column AbstrakArtikel ini mengkaji ulang penelitian-penelitian yang telah dilakukan mengenai simulasi enhancement factor absorpsi disertai reaksi reversible order dua kondisi non-isotermal dan pemodelan packed column untuk absorpsi gas CO2 kedalam larutan K2CO3 pada packed column. Harga enhancement factor diprediksi dengan menggunakan model eddy diffusivity (model King untuk perpindahan massa antar fasanya). Sistim persamaan diferensial yang dibentuk dari pemodelan ini diselesaikan dengan metoda Kolokasdi Ortogonal. Hasil prediksi harga E dari penelitian ini sangat mendekati hasil prediksi menggunakan model Penetrasi oleh Vas Bhat (1997). Penelitian pemodelan packed column dilaksanakan secara eksperimen dan simulasi. Penelitian secara eksperimen dilaksanakan untuk validasi hasil simulasi. Bahan yang digunakan adalah campuran CO2 dan udara serta larutan potasium karbonat. Larutan potasium karbonat dialirkan kedalam packed column dari atas dan dikontakkan secara berlawanan arah dengan aliran campuran CO2-udara dari bawah. Cairan keluar kolom dianalisa dengan titrasi. Sedangkan percobaan simulasi dilaksanakan dengan mengembangkan model neraca massa dan energy mikroskopik pada kolom. Sistim persamaan diferensial order satu yang dihasilkan diselesaikan dengan metoda Rung Kutta order empat. Solusi model ini memerlukan informasi mengenai laju transfer massa antar fasa gas-liquid yang dalam hal ini menggunakan model King. Data kelarutan CO2, data perpindahan massa, data kinetika dan kesetimbangan reaksi yang diperlukan pada penelitian ini diperoleh dari literatur (Danckwertz, 1970; Kohl and Riesenfeld,1985; dan Treyball, 1981). Pada penelitian ini dipelajari pengaruh laju alir absorben dan konsentrasi K2CO3 dalam larutan absorben masuk terhadap persen penyisihan gas CO2. Deviasi antara hasil prediksi simulasi dan data percobaan pada penelitian ini dibawah 10% untuk laju alir absorben dari 3 sampai dengan 5 liter/menit dan untuk laju alir 5 sampai dengan 7 liter menit deviasi nya antara 10-30%.Kata kunci: perpindahan massa, eddy diffusivity, absorpsi, non-isotermal, packed column